Beans. Producer Organizations Promoting Integrated Development with a Value Chain Approach - Miranda Salgado, Félix; Cajin, Nilo; Rueda Pereira, Antonio; Rodríguez Alfaro, Scarleth; Herrera, Alexis (Catholic Relief Services, 2012)
This publication is the result of a participatory experience capitalization, facilitated by the International Center for Tropical Agriculture for the project “Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships” (ACORDAR). The report addresses the building and strengthening of the beans value chain in northern Nicaragua using innovative strategies and aims to disseminate and share study results. Feedback will facilitate the application of this approach in other regions, strengthen the existing knowledge base and influence policy makers at both local and national levels.